Superroot, a recessive mutation in Arabidopsis, confers auxin overproduction. - Boerjan, W (1995)
We have isolated seven allelic recessive Arabidopsis mutants, designated superroot (sur1-1 to sur1-7), displaying several abnormalities reminiscent of auxin effects. These characteristics include small and epinastic cotyledons, an elongated hypocotyl in which the connection between the stele and cortical and epidermal cells disintegrates, the development of excess adventitious and lateral roots, a reduced number of leaves, and the absence of an inflorescence. When germinated in the dark, sur1 mutants did not develop the apical hook characteristic of etiolated seedlings. We were able to phenocopy the Sur1- phenotype by supplying auxin to wild-type seedlings, to propagate sur1 explants on phytohormone-deficient medium, and to regenerate shoots from these explants by the addition of cytokinins alone to the culture medium. Analysis by gas chromatography coupled to mass spectrometry indicated increased levels of both free and conjugated indole-3-acetic acid. sur1 was crossed to the mutant axr2 and the altered-auxin response mutant ctr1. The phenotype of both double mutants was additive. The sur1 gene was mapped on chromosome 2 at 0.5 centimorgans from the gene encoding phytochrome B.